Analysis Of The Results Of Scientific Research On Noise Reduction In Machine-Building Sectors And Related Enterprises - Sh.G. Musayev (Genius Journals, 2025)
This article extensively analyzes the problem of production noise arising in machine-building workshops and related industrial enterprises, the results of scientific research on its reduction, and the effectiveness of existing solutions. In scientific literature, it is noted that noise arising in production processes negatively affects human health, labor productivity, and occupational safety. According to international standards (ISO 9612:2009) and national sanitary standards, the level of noise pressure at workplaces should not exceed 85 dBA, however, observations conducted in blacksmithing and pressing shops showed results in the range of 95-100 dBA. This is significantly higher than the normative requirement and poses a risk to the hearing and nervous system of workers. According to the analysis of research, noise reduction was carried out in three main directions: noise reduction at the source, absorption in the path of propagation, and provision of personnel with personal protective equipment. Although structural improvements, reduction of resonant frequencies, and the use of noiseabsorbing panels have yielded effective results in the woodworking and light machinebuilding industries, their application in heavy industry conditions is limited. In metalworking and blacksmithing workshops, acoustic screens, vibration-absorbing materials, and methods for stabilizing flow in hydraulic systems are considered promising solutions
Keywords: production noise; acoustic screen; vibration